POLICULTURAL PROFESSIONAL COMPETENCE OF A MODERN TEACHER (Pedagogy of Higher and Secondary Education, 2004)
The problem of the professional competence of a teacher in a context of the future teacher's training for teaching and upbringing activities in the polycultural pedagogical society is considered in the article.